An experimentally validated dislocation density based computational framework for predicting microstructural evolution in cold spray process. (15th August 2021) - Msolli, Sabeur; Zhang, Zhi-Qian; Seng, Debbie Hwee Leng; Zhang, Zheng; Guo, Junyan; Reddy, C.D.; Sridhar, N.; Pan, Jisheng; Tan, Boon Hee; Loi, Qizhong
Graphical abstract: Highlights: A dislocation density based model was validated and implemented as user subroutine. Application of Eulerian formulation to overcome mesh distortion for multi-particle impacts. Investigation of the effect of CSAM process parameters on microstructure evolution. Both simulation and experiments show GNDs are higher in the coating at the particle boundary. Abstract: We present an experimentally validated computational model for microstructural evolution in the cold spray additive manufacturing process of Al6061 alloy coating. The microstructural characteristics are determined with a dislocation density-based model that is shown to be applicable to cold spray modeling and is implemented in a Eulerian finite element framework to predict microstructural evolution for both single and multiple particle cold spray deposition. A comparison of the numerical and experimental results from Scanning Electron Microscope (SEM), Electron Backscatter Diffraction (EBSD) and Kernel Average Mis-orientation (KAM) analyses, reveals the evolution of cell size and mis-orientation resulting in grain refinement at the particle–substrate and particle–particle interfaces. Although there is a large plastic deformation due to high speed impact, the dislocation density in the particle decreases with distance from the impacting interface and this feature is observed in both the simulation results and the experimental characterization data. The validated model can be leveraged to predict microstructural evolution under different process conditions including spray angle, pre-heat temperature, and impact velocity.